Google Form ka Wasīlah at-Taqyīm fīTa’līm al-Qirā`ah wa al-Qawā’id bi al-Jāmi’ah - Muhammad Nur Kholis; Achmad Jakfar Sodik; Jamaluddin Shiddiq; Hafidah Hafidah (IAIN Salatiga, 2020)
This paper tries to explain the process of using google form as a assessment instruments for Arabic reading skills (qirâ`ah) and arabic grammar (qawâ’id). The purpose of this study is to find out the features that can be used as a assessment instruments for qirâ`ah and qawâ’id, and their proficiency assessment instruments. This study uses a qualitative approach to the type of descriptive research. The objects of this study were students at IAIN Surakarta who participated in the Arabic Practicum Program organized by the Language Development Center (P2B). The results showed that the features of google form that can be used as a medium for evaluating the competence of reading Arabic texts and Arabic rules are short answer, multiple choice, checkboxes and dropdown features.